2 states : the story of my marriage - Bhagat, Chetan (New Delhi : Rupa & Co., 2009)
Story about inter-community marriage in modern India.
"First published 2009, eleventh impression 2009"--T.p. verso.
Keywords: Interethnic marriage -- India -- Fiction; Indic fiction (English); Fiction